Agrarian reforms in India : critical analysis. - Sastry, D.S. (New Delhi, 1991)
Inspite of constitutional prerogatives the progress in the field of agriculture has not been satisfactory. This book widly discusses about our country's approach to agricultural Land pro blems with critical analysis. Also the controversy over property rights pertaining to agricultural land is one of the central themes of our constitu tional development particularly after independence. The statutory and legal matters akin to the field of land reforms are also dealt with. The successive Governments in India since Independence are unable to introduce radical land reforms. In this book, it is evidently proved that in the absence of morality, faith, trust and Dharma, such successive legislations would become useless and purpose less.
Keywords: Agrarian reform India